The Analysis of Deep Neural Networks by Information Theory: From Explainability to Generalization - Yu, Shujian (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Despite their great success in many artificial intelligence tasks, deep neural networks (DNNs) still suffer from a few limitations, such as poor generalization behavior for out-of-distribution (OOD) data and the "black-box" nature. Information theory offers fresh insights to solve these challenges. In this short paper, we briefly review the recent developments in this area, and highlight our contributions.